Letters to the editor: The National Early Warning Score 2 (NEWS2). Issue 3 (2019) - Smith, Gary B; Redfern, Oliver C; Pimentel, Marco AF; Gerry, Stephen; Collins, Gary S; Malycha, James
No abstract available